Psychological Barriers of Students in Listening to English Lessons in Online Learning Process - Nur Ainun Rahmat; Andi Muliati; Nur Aeni (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
The aim of this study is to find out what are the psychological barriers faced by students of SMP Negeri 8 Palopo when listening to English lessons in the online learning process. Qualitative design with analytical description was the method used by the researcher. The population was the third-grade students at SMP Negeri 8 Palopo in academic year 2022/2023. This research used simple random sampling technique. In this case, the researcher chose two classes to distribute the questionnaire and eight people were selected from the questionnaire results to be interviewed. Instrument of this research was questionnaire and interview. The results of data analysis shows that students' psychological barriers when listening to English lessons in the online learning process are; students' perspective on English lessons, students feel anxious, less-interest in English, lack of concentration and lack of vocabulary and conversation skills. The research results that trigger the presence of psychological barriers to learning are learning methods and local support.Keywords— Psychological Barriers, Students, Listening to English Lessons